An algorithmic treatment strategy for the inhibition of type-II deiodinase enzyme on thyroid secretion hormones. (April 2021) - Jamshidi, Arta A.; Rokni Lamouki, Gholam Reza
Highlights: We propose a dynamical strategy to control the thyroid and compensate for inhibitions of Type-II Deiodinase enzyme (enzyme D2 ) on thyroid secretion hormones due to an illness such as cancer or sepsis. We provide a mathematical model for the thyroid which considers enzyme D2 . We design a two-line treatment/control strategy that reduces the effect of the inhibitory illness, and the level of TSH. We provide an algorithm to find the boundaries of the control variables for various behaviors of the thyroid. Given various control levels, we observe that the geometric properties of the projected limit cycles of thyroid behavior on the T3 -T4 plane can be classified into four major regions, namely; Normal, Jumpy, Critical, and Damping. We propose a treatment strategy that navigates through these regions in a way that is tolerable for the body. Abstract: In this work we provide a treatment strategy to compensate for the effect of the inhibition of Type-II Deiodinase enzyme on thyroid secretion hormones due to an illness such as cancer or sepsis. Our two-line treatment strategy reduces the effect of the inhibitory illness, and the level of TSH. This joint action creates a control region, where we find a balance between the control nodes that is tolerable for the body. We provide an algorithm to find the boundaries of the control variables for various behaviors of the thyroid and provide an appropriate treatment strategy. Given various control levels, we observe that the geometric properties of the projected limit cycles of thyroid behavior on the T 3 -T 4 plane can be classified into four major regions, namely; Normal, Jumpy, Critical, and Damping. The amount of Thyroxine produced is inadequate in the jumpy region and is detrimental to the body in the critical and damping regions. Our strategy is viable, compensates for the inhibition of Deiodinase enzyme and stabilizes thyroid performance.